Convulsive Stress Mimics Brain Hypoxia and Promotes the P-Glycoprotein (P-gp) and Erythropoietin Receptor Overexpression. Recombinant Human Erythropoietin Effect on P-gp Activity - Merelli, Amalia; Ramos, Alberto Javier; Lazarowski, Alberto; Auzmendi, Jeronimo (Frontiers in Neuroscience, 2019)
Erythropoietin (EPO) not only is a hormone that promotes erythropoiesis but also has a neuroprotective effect on hypoxic neurons related with their known antiapoptotic action. In a focal brain-hypoxia model, our group have previously demonstrated that recombinant-human EPO (rHu-Epo) can protect neurons with a Hypoxia Inducible Factor 1 (HIF-1) expression of EPO-receptor (EPO-R) and P-glycoprotein (P-gp). We and others also have reported that repetitive seizures can mimic a hypoxic-like condition by HIF-1nuclear translocationand high neuronal expression P-gp. Here, we document not only that excitotoxic stress can also induce the expression of EPO-R, but rHu-EPO can reverse the P-gp transport activity under the mentioned hypoxic-like conditions. A single status epilepticus (SE) of twenty minutes was induced in adult rats using the lithium-pilocarpine model. In vitro, primary cultures of neurons were briefly exposed to an excitotoxic concentration of glutamate (300 µM), while cultured astroglial-cells were treated for 6h with 0.3 mM of CoCl2, and later, the inhibitory effect of increased concentrations of rHu-Epo on Rhodamine 123 (Rho-123) P-gp dependent efflux was assayed. The specific P-gp blocker Tariquidar (1 µM) or saline, were used as positive or negative inhibitory controls respectively. SE promoted high co-expression of P-gp and EPO-R in cortical neurons and astrocytes. In vitro, neurons treated with glutamic acid exhibited nuclear translocation of HIF-1 and NFB and high overexpression P-gp and EPO-R. In cultured astroglial-cells treated with CoCl2, rHu-Epo recovered significantly the Rho-123 retention in a similar way of tariquidar. Our results confirm that convulsive stress promotes nuclear translocations of HIF- and NFkB transcription factors with a concomitant induction of neuronal expression of P-gp and EPO-R, suggesting that convulsive stress could mimic a hypoxic condition without oxygen deprivation. Furthermore, we demonstrate for the first time that rHu-Epo can inhibit the Rho-123 efflux activity. All these data suggest that EPO/EPO-R system stimulation could play a central role not only in brain cell protection after different stress signals, but also it could reverse the pharmacoresistant phenotype in refractory epilepsy as well as in other pharmacoresistant hypoxic brain diseases simultaneously expressing EPO-R and P-gp.